Influence of Low-Cost Carrier Attributes towards Airline Choice Decision in Bandung-Surabaya Route - Idham, Idham; Belgiawan, Prawira Fajarindra; Putri, Christina Ari Pramono (Jurnal Manajemen Teknologi, 2021)
Abstract. The number of Indonesian domestic passengers which increased rapidly has encouraged for the airlines to expand their market share by opening routes in the local region and one of the promising region is Bandung. In early 2019, the Low-Cost Carrier has implemented paid baggage policy. The changes of airline conditions and regulations could affect consumer purchasing decisions. The airline have to redesign its strategies and conduct a strategy adjusment to identify the consumer's needs and wants these days. Based on the problem description, this research aims to identify what significant attributes influence passenger's purchasing decision-making and determine what elastic and inelastic attributes. Data collection using an online questionnaire then spread to 235 respondents and were analyzed with Mixed Logit Model using BIOGEME software. The results shows that airline's departure time is a significant attribute towards passenger's airline choice. Ticket price also plays a key role in selecting an airline for passengers when the ticket price increases, Passenger will consider choosing other alternative airlines that are more affordable. The results could be used by an airline company to attract the passenger by improving its marketing strategy.Keywords: Low-cost carrier, airline choice, airline attribute, mixed logit, demand elasticitiesAbstrak. Pertumbuhan pesat penumpang pesawat udara domestik di Indonesia memicu semua maskapai untuk memperluas pangsa pasar dengan membuka berbagai rute domestik baru, salah satu wilayah yang menjanjikan adalah Kota Bandung. Pada awal 2019, maskapai berbiaya rendah menerapkan kebijakan bagasi berbayar. Dinamika perubahan kondisi dan regulasi yang telah disebutkan sebelumnya dapat mempengaruhi keputusan pembelian konsumen. Oleh karena itu, maskapai harus merancang ulang strategi pemasaran untuk penyesuaian keinginan dan kebutuhan konsumen saat ini. Berdasarkan permasalahan tersebut, penelitian ini bertujuan untuk mengidentifikasi atribut-atribut apa saja yang signifikan mempengaruhi penumpang dalam membuat keputusan pembelian dan menentukan atribut-atribut apa saja yang elastis dan tidak elastis. Pengumpulan data menggunakan kuesioner daring lalu disebarkan ke 235 responden dan akan dianalisis dengan Mixed Logit Model menggunakan perangkat lunak BIOGEME. Hasil penelitian menunjukkan jika atribut waktu keberangkatan penerbangan signifikan terhadap pemilihan maskapai oleh penumpang. Selain itu, harga tiket juga memainkan peran penting dalam pemilihan maskapai dimana jika harga tiket suatu maskapai naik, maka penumpang akan mempertimbangkan untuk memilih maskapai lainnya yang lebih terjangkau. Hasil penelitian ini dapat digunakan oleh maskapai untuk menarik atensi penumpang dengan memperbaiki strategi pemasaran mereka.Kata kunci: Low-cost carrier, airline choice, airline attribute, mixed logit, demand elasticities